STUDY OF RESILIENCE IN ADOLESCENTS IN SEVERAL COUNTRIES IN THE WORLD - HILDA SAFRIANI; ROMA ULINNUHA (Al-Tazkiah Jurnal Bimbingan dan Konseling Islam, 2023)
This article will provide an overview of adolescent resilience in several countries in the world. This research uses a qualitative approach with data collection techniques, namely literature study with the results of previous research. The location settings for these studies are 3 (three) countries in the world, namely Zambia, Canada and Iran. Specifically for Canada, the teenagers studied were teenagers from military family backgrounds. The research results show two factors that can increase adolescent resilience, namely, internal factors and external factors. The internal factor is the self-confidence of each teenager who has awareness after facing problems and adapting positive values ??within themselves, as well as strengthening the spiritual side related to their relationship with God. Meanwhile, external factors include social support from the community, government program intervention, and friends who are in the same boat as them.